Dissolved/dispersed polycyclic aromatic hydrocarbon spatial and temporal changes in the Western Gulf of Mexico - Gold-Bouchot, Gerardo; Arcega-Cabrera, Flor; Ceja-Moreno, Víctor (Frontiers in Marine Science, 2023)
Oil extraction and transport activities in the Gulf of Mexico (GoM), along with major marine oil spills and riverine inputs are exerting an environmental pressure to this system by increasing the concentration of oil related pollutants such as polycyclic aromatic hydrocarbons (PAH). Although, to fully identify these changes related with oil activities a current PAH level should be stablished. Here we present the PAH concentration, and the low molecular weight (LMW) and high molecular weight ratios obtained in the Perdido Fold Belt area in surface and bottom water at four cruises from May 2016 to September 2017. The Perdido 1 (P1) cruise was conducted in May 2026, the Perdido 2 (P2) cruise in September-October 2016, the Perdido 3 (P3) cruise in June 2017, and the Perdido 4 (P4) cruise in September 2017. Samples were taken during each cruise at up to 3,500 m depth, the deepest ever recorded for the Mexican GoM. Results show the highest concentrations of PAH, LMW PAH, and HMW PAH were found in the P4 cruise (1.15, 1.05 and 0.10 µg/L, respectively), well below the 300 µg/L guideline for acute exposure. LMW/HMW ratios show that only P1 cruise indicate pyrogenic hydrocarbons whilst P2, P3 and P4 where petrogenic. The spatial distribution of total PAH, LMW and HMW showed higher values in the southern and northeastern areas, except for P4 that showed high values related with riverine inputs. The complex hydrodynamic in the region was found to have a significant effect on PAH seasonal changes, river contributions, eddy circulation and fronts promote their dispersion.